2022
DOI: 10.11604/pamj.2022.41.294.28686
|View full text |Cite
|
Sign up to set email alerts
|

Profil socio-démographique et économique des adultes drépanocytaires régulièrement suivis au Centre Hospitalier Universitaire de Libreville

Abstract: La drépanocytose est une maladie génétique héréditaire de transmission autosomique récessive. L´organisation depuis septembre 2016 au Centre Hospitalier Universitaire de Libreville (CHUL), d´une consultation d´hématologie dédiée à l´adulte drépanocytaire, a été l´occasion de mener cette étude dont le but était de décrire le profil socio-démographique et économique des patients régulièrement suivis. Il s´agissait d´une étude rétrospective, descriptive et non comparative, qui s´est déroulée de septembre 2016 à j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 4 publications
0
4
1
Order By: Relevance
“…The highest age of patients in our cohort was 75 years. This shows that SCD can be experienced well into old age in Africa, although other studies in Africa show a maximum age below that found in our cohort [ 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…The highest age of patients in our cohort was 75 years. This shows that SCD can be experienced well into old age in Africa, although other studies in Africa show a maximum age below that found in our cohort [ 15 , 16 ].…”
Section: Discussioncontrasting
confidence: 68%
“…According to gynecological history, we noted an average of 2.4 pregnancies for 1.3 deliveries; therefore, an average of 1.1 pregnancies did not reach term, with the occurrence of an abortion or stillbirth. Tis rate of interrupted pregnancies not reaching term has already been reported in women with sickle cell disease [15]. Strict, well-coordinated management by haematologists and gynaecologists-obstetricians is essential for monitoring these SCD women, whose pregnancies carry a high risk of fetal and maternal mortality.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations